2017
DOI: 10.1080/01652176.2017.1334981
|View full text |Cite
|
Sign up to set email alerts
|

A field study on the anthelmintic resistance of Parascaris spp. in Arab foals in the Riyadh region, Saudi Arabia

Abstract: Background: In the last decade, Parascaris spp. resistance to anthelmintics has been recorded in many countries. In Saudi Arabia, there are limited data available on Parascaris spp. resistance to anthelmintics. Objective: To determine the current status of ivermectin, abamectin and praziquantel combined, and fenbendazole resistance to Parascaris spp. in horses in Saudi Arabia. Methods: Three hundred and forty-one foals from eleven different farms were examined by faecal egg count (FEC). The foals were all Arab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…In Parascaris sp., ML resistance was first reported in the early 2000s 7 and since then has developed into a global challenge. Its presence has been demonstrated in several European countries 8 – 13 , North America 14 16 , as well as New Zealand 17 , Australia 18 and more recently Ethiopia 19 and Saudi-Arabia 20 . Similarly, the development and spread of ML resistance has been reported in many other parasitic nematodes, including Teladorsagia circumcincta 21 and Haemonchus contortus in sheep 22 , Dirofilaria immitis 23 in dogs and even in human filarial nematodes such as Onchocerca volvulus 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In Parascaris sp., ML resistance was first reported in the early 2000s 7 and since then has developed into a global challenge. Its presence has been demonstrated in several European countries 8 – 13 , North America 14 16 , as well as New Zealand 17 , Australia 18 and more recently Ethiopia 19 and Saudi-Arabia 20 . Similarly, the development and spread of ML resistance has been reported in many other parasitic nematodes, including Teladorsagia circumcincta 21 and Haemonchus contortus in sheep 22 , Dirofilaria immitis 23 in dogs and even in human filarial nematodes such as Onchocerca volvulus 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to repeated reports of resistance to macrocyclic lactones (MLs) since 2002 ( Boersema et al, 2002 ; Osterman Lind and Christensson, 2009 ; Reinemeyer, 2009 ) and more recently to pyrantel (PYR) ( Lyons et al, 2008 ; Martin et al, 2018 ; Hautala et al, 2019 ), benzimidazoles (BZs) are currently the first choice of treatment for P. univalens infection in many countries. Despite frequent use of BZs, only a few cases of resistance have so far been reported in P. univalens ( Armstrong et al, 2014 ; Alanazi et al, 2017 ). In Ascaris lumbricoides and Ascaridia dissimilis , the ascarid parasites of humans and turkeys, single cases of reduced efficacy have been noted ( Collins et al, 2019 ; Krucken et al, 2017 ), while there have been no reported cases of resistance in the poultry and pig roundworms Ascaridia galli and Ascaris suum ( Tarbiat et al, 2017 ; Zhao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The benzimidazole fenbendazole is generally effective against Parascaris spp. in Europe [3,15], but sporadic cases of treatment failure have been reported from Australia [14] and Saudi Arabia [16]. Considering the risk of lethal complications in foals infected with Parascaris spp.…”
Section: Introductionmentioning
confidence: 99%